Glucocappasalin Induces G2/M-Phase Arrest, Apoptosis, and Autophagy Pathways by Targeting CDK1 and PLK1 in Cervical Carcinoma Cells - Xu, Guangya; Yan, Xueling; Hu, Zhongjia; Zheng, Lulu; Ding, Ke; Zhang, Yamei; Qing, Yi; Liu, Tao; Cheng, Lijia; Shi, Zheng (Frontiers in Pharmacology, 2021)
Glucocappasalin (GCP), a natural product derived from the seed of Descurainia sophia (L.) Webb. ex Prantl, exhibits potential antitumor activity in HeLa cervical carcinoma cells. In this study, we investigated the anti-cervical cancer property of GCP through the induction of cell cycle arrest, apoptosis, and autophagy in vitro and in vivo, and elucidated the underlying molecular mechanisms. We demonstrated that treatment with GCP inhibited the growth of HeLa, Siha, and Ca Ski cell lines in a dose-dependent manner, with HeLa cells displaying particular sensitivity to the GCP treatment. Subsequently, the expression of cyclin-dependent kinase 1 (CDK1) and polo like kinase 1 (PLK1) were evaluated in HeLa cells using the CDK1 kinase assay kit, the fluorescence polarization assay, real-time quantitative PCR, and western blotting. Our results demonstrate that GCP could be employed to attenuate the expression of CDK1 and PLK1 in a dose- and time-dependent manner. The complementary results obtained by flow cytometry and western blotting allowed us to postulate that GCP may exhibit its antitumor effects by inducing G2/M cell cycle arrest. Moreover, HeLa cells treated with GCP exhibited a loss in mitochondrial membrane potential, together with the activation of caspases 3 and 9, and poly ADP-ribose polymerase (PARP). Additionally, we found that GCP could increase the formation of acidic vesicular organelles (AVOs), as well as the levels of Beclin1, LC3-II, p62, and Atg5 proteins in HeLa cells. Further studies indicated that GCP triggered autophagy via the suppression of the PI3K/AKT/mTOR signaling pathways. The autophagy inhibitor 3-methyladenine (3-MA) was used to determine whether autophagy affects the apoptosis induced by GCP. Interestingly, the inhibition of autophagy attenuated apoptosis. In vivo anti-tumor experiments indicated that GCP (60 mg/kg, i.p.) markedly reduced the growth of HeLa xenografts in nude mice without apparent toxicity. Taken together, we demonstrate that GCP induces cell cycle G2/M-phase arrest, apoptosis, and autophagy by acting on the PI3K/AKT/mTOR signaling pathways in cervical carcinoma cells. Thus, GCP may represent a promising agent in the eradication of cervical cancer.